(3GdpbnQi dbGUO Ce GdbQis - (3eMH GdOjf GdWHQj , CMeO Hf YHO Gddg Hf eMeO GdWHQj,J (B694 (3g` s ((3eMeO Hf bGSe GdTQja GdfRQJi s)
(3ChdgG (B:s
(3GdHGH GdKGef YTQ ai Gdhbha HYQaI s
(3BNQgG (B:s
(3ef MOjK QShd Gddg Udi Gddg Ydjg hSde (B: (3Gddge CZaQ dfG eG bOefG heG CNQfG heG CNWCfG heG JgeOfG CfJ GdebOe hCfJ GdeDNQ , dG Edg EdG CfJ s
(3GdLRA GdKGfi ef GdfSNI GdSGHbI faSgG JMJ Qbe (B119 (3JGQjNs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B159 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B298s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs